2019
DOI: 10.1007/s10875-019-00709-1
|View full text |Cite
|
Sign up to set email alerts
|

BCG Moreau Vaccine Safety Profile and NK Cells—Double Protection Against Disseminated BCG Infection in Retrospective Study of BCG Vaccination in 52 Polish Children with Severe Combined Immunodeficiency

Abstract: Objectives The aim of the study was to estimate the rate of adverse reactions to live BCG Moreau vaccine, manufactured by Biomed in Poland, in severe combined immunodeficiency (SCID) patients. Material The profiles of 52 SCID patients vaccinated at birth with BCG, hospitalized in Children's Memorial Health Institute, Warsaw (CMHI), in the years 1980-2015 were compared with those of 349 BCG-vaccinated SCID patients from other countries analyzed by Beatriz E. Marciano et al. in a retrospective study (Marciano et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…A high proportion of patients with SCID (nearly 50%) has been reported to develop complications related to BCG 34 . However, much lower prevalence (10%) of BCG‐related complications were seen in our previous study on a large cohort of SCID patients which has also been reported by some other studies 38,39 . The complications of BCG in SCID patients depend on the age of vaccination, type of vaccine used, the residual T lymphocyte count and NK cell numbers 5 .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A high proportion of patients with SCID (nearly 50%) has been reported to develop complications related to BCG 34 . However, much lower prevalence (10%) of BCG‐related complications were seen in our previous study on a large cohort of SCID patients which has also been reported by some other studies 38,39 . The complications of BCG in SCID patients depend on the age of vaccination, type of vaccine used, the residual T lymphocyte count and NK cell numbers 5 .…”
Section: Discussionsupporting
confidence: 58%
“…34 However, much lower prevalence (10%) of BCG-related complications were seen in our previous study on a large cohort of SCID patients which has also been reported by some other studies. 38,39 The complications of BCG in SCID patients depend on the age of vaccination, type of vaccine used, the residual T lymphocyte count and NK cell numbers. 5 The absolute T-cell count in patients with BCGosis was found to be significantly lower than the SCID patients without BCG complications.…”
Section: Treatment and Outcomementioning
confidence: 99%
“…Severe, life-threatening infections following LAV, such as BCG, OPV, measles vaccine (MeV), and an oral rotavirus vaccine (ORV), have been reported in PID patients and ascribed to a variety of disturbances of immune response, such as defective production of interferons, T and B cells deficiency and dysfunction, and NK cell deficiency. [112][113][114] From the pediatrician's perspective, an early PID diagnosis afforded by NBS is important to avoid live viral and bacterial vaccines. A pediatrician's awareness is also required in case of newborns and infants having a positive family history of PIDs to postpone all live vaccines until the child has survival, somatic hypermutation, memory B cell development, IgG1, IgG3, and IgA production, and antibody affinity maturation.…”
Section: Preventive Measures and Therapeutic Options: Current Status And Future Perspectivesmentioning
confidence: 99%
“…MF59: inducing CCL3 and CXCL8 chemoattractants, 49 AS03: inducing neutrophil chemoattractants 49 Effect on recruitment by suppression of CXCL1 and CXCL2 production 57 Impairment of phagocytic and chemotactic abilities 45 Elevated levels of neutrophils 58 NK cells *Inducing the production of IFN-γ, 59 *inducing trained immunity in NK cells 46…”
Section: Bcg Vaccinementioning
confidence: 99%